2022
DOI: 10.1096/fasebj.2022.36.s1.r4738
|View full text |Cite
|
Sign up to set email alerts
|

Activation of dorsal motor nucleus cholinergic neurons ameliorates the severity of acute pancreatitis

Abstract: Clusters of neuron cell bodies, termed nuclei, residing in the brainstem are the origin of cranial nerves which transmit action potentials controlling organ function. Neurons residing in the brainstem dorsal motor nucleus (DMN) project in the vagus nerve to communicate with the pancreas, liver, gastrointestinal tract and other organs. Cholinergic signaling in the vagus nerve‐mediated inflammatory reflex also controls immune system responses by inhibiting the production of cytokines in the spleen, although the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Using optogenetic stimulation we recently revealed the role of DMN cholinergic neurons in suppressing serum TNF levels during murine endotoxemia (10). This study and other reports employing optogenetic stimulation emphasize the importance of studying targeted brain neuromodulation in new strategies for controlling inflammation (6,(37)(38)(39). While optogenetic stimulation provides a cell specific means of neuromodulation, the clinical applicability of this approach remains challenging.…”
Section: Discussionmentioning
confidence: 74%
“…Using optogenetic stimulation we recently revealed the role of DMN cholinergic neurons in suppressing serum TNF levels during murine endotoxemia (10). This study and other reports employing optogenetic stimulation emphasize the importance of studying targeted brain neuromodulation in new strategies for controlling inflammation (6,(37)(38)(39). While optogenetic stimulation provides a cell specific means of neuromodulation, the clinical applicability of this approach remains challenging.…”
Section: Discussionmentioning
confidence: 74%
“…2 Such approaches will allow further interrogation of this circuitry and should be applied with pVNS to clarify afferent and efferent vagal signaling after orthopedic surgery. 7,28,60 Using our pVNS protocol, we found that weekly pVNS resolved postoperative allodynia on day 22 after surgery. Notably, it took 3 weeks and 4 pVNS treatments to effectively reduce bilateral mechanical paw allodynia to baseline levels.…”
Section: Discussionmentioning
confidence: 92%
“…Despite historical controversy about the capacity of CVN DMV to impact HR, our results demonstrate that optogenetic and chemogenetic activation of Chat+ DMV neurons each caused robust bradycardia (~56% and ~65.5% of resting HR, respectively) in awake, behaving mice. Cardioinhibitory responses using optogenetic techniques in urethane-anesthetized rats and ketamine/xylazine-anesthetized mice demonstrated variable strength of the response (Machhada et al, 2020;Thompson et al), implicating differences in anesthesia for differences in effect size. Alternatively, previous species used (namely cats and rats) may exhibit a lesser degree of DMV-activation driven bradycardia than mice because of differences in vagal tonus.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these anatomical studies, functional studies remain conflicting. Some argue that direct electrical stimulation of DMV does not change chronotropy (Geis and Wurster, 1980;Laughton and Powley, 1987), while others demonstrate local activation (chemical, electrical, optogenetic, or chemogenetic) elicits bradycardias even if only modestly (Falvey et al, 2023;Machhada et al, 2020;Machhada et al, 2016;Sporton et al, 1991;Thompson et al, 2023). However, no activation technique in awake animals used to date rules out incidental stimulation of either neighboring nucleus tractus solitarius (NTS) neurons or inhibitory interneurons within DMV.…”
Section: Introductionmentioning
confidence: 99%